Response of Two Year Old Pinus patula to N, P and K Fertilization - Singh, S. B.; Prasad, K. G.; Gupta, G. N.; Maurya, G. S. (Indian Forester, 1986)
Influence of N, P, K fertillzation was studied in two year old stand of Pinus patula at Paymund, Ooty. Trees smaller than 2m responded to 20kg of N/ha and also to 15kg of P2O5 whereas, the trees more than 3m tall showed growth response to nitrogen only. Nitrogen and phosphorus interaction was not significant, Phosphorus Ã— potassium interaction was positive on growth of trees smaller than 2m. Nitrogen and potossium relationship was antagonistic in all plants. The study indicates the need to carry out comprehensive experimental trials on methods of fertilization in pine stands.